2014
DOI: 10.1038/ncomms5415
|View full text |Cite
|
Sign up to set email alerts
|

Super switching and control of in-plane ferroelectric nanodomains in strained thin films

Abstract: With shrinking device sizes, controlling domain formation in nanoferroelectrics becomes crucial. Periodic nanodomains that self-organize into so-called 'superdomains' have been recently observed, mainly at crystal edges or in laterally confined nanoobjects. Here we show that in extended, strain-engineered thin films, superdomains with purely in-plane polarization form to mimic the single-domain ground state, a new insight that allows a priori design of these hierarchical domain architectures. Importantly, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 46 publications
5
100
0
2
Order By: Relevance
“…[99] Moreover, Noheda's group has shown that superdomains in PbSrxTi1-xO3 can dominate ferroelectric switching. [100]. These inplane superdomains are strain-neutral, like those in the right-hand side of our Figure 1.…”
Section: Discussionsupporting
confidence: 65%
“…[99] Moreover, Noheda's group has shown that superdomains in PbSrxTi1-xO3 can dominate ferroelectric switching. [100]. These inplane superdomains are strain-neutral, like those in the right-hand side of our Figure 1.…”
Section: Discussionsupporting
confidence: 65%
“…The Journal of Physical Chemistry 48,56 Since the striped pattern in the MAPbI 3 grains could not be observed in the topography, we conclude that both twinning domains are either oriented in the same non-90°…”
Section: Page 13 Of 33 Acs Paragon Plus Environmentmentioning
confidence: 79%
“…Pulsed laser deposition (PLD) technique was employed to grow highly oriented PLBZT films on LaNiO 3 (LNO)/LaAlO 3 (LAO) substrate. Initially, LAO substrate was ultrasonicated in acetone for two minutes and then in methanol for 30 minutes to remove the native oxides and impurities present on the substrate before laser ablation.…”
Section: Experimental Methodsmentioning
confidence: 99%